2008
DOI: 10.1063/1.2929744
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and diffusion length of photogenerated minority carriers in single-crystalline n-type β-FeSi2 bulk

Abstract: We have evaluated the lifetime and diffusion length of photogenerated minority carriers ͑holes͒ in single-crystalline n-type ␤-FeSi 2 bulk grown by chemical vapor transport. The diffusion length measured by optical-beam-induced current agreed well with that measured by electron-beam-induced current, that is, 51 and 38 m, respectively, for samples annealed at 800°C for 8 h. The decay curve of photoconductivity obtained by 1.31 and 1.55 m light pulses was well fitted by assuming a carrier lifetime of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Photocurrents were observed for photon energies greater than 1.25 eV and increased sharply for photon energies greater than 1.3 eV, reaching a maximum photoresponsivity of 0.37 A/W at 1.55 eV when the bias voltage was 2.0 V. These values are the highest ever reported for semiconducting silicides and are more than three times higher than the value of 0.1 A/W at 0.98 eV obtained for a bulk n-type b-FeSi 2 single crystal. 25 Compared with the result for sample B, the photoresponsivity is increased by more than 30 times. This is attributed to suppression of the thermal diffusion of Sb atoms in the BaSi 2 layers due to the presence of the c-Si layer grown by SPE, and the resulting heavier Sb concentration in the n þ -BaSi 2 layer enables the formation of the high-quality TJ in sample A.…”
mentioning
confidence: 82%
“…Photocurrents were observed for photon energies greater than 1.25 eV and increased sharply for photon energies greater than 1.3 eV, reaching a maximum photoresponsivity of 0.37 A/W at 1.55 eV when the bias voltage was 2.0 V. These values are the highest ever reported for semiconducting silicides and are more than three times higher than the value of 0.1 A/W at 0.98 eV obtained for a bulk n-type b-FeSi 2 single crystal. 25 Compared with the result for sample B, the photoresponsivity is increased by more than 30 times. This is attributed to suppression of the thermal diffusion of Sb atoms in the BaSi 2 layers due to the presence of the c-Si layer grown by SPE, and the resulting heavier Sb concentration in the n þ -BaSi 2 layer enables the formation of the high-quality TJ in sample A.…”
mentioning
confidence: 82%
“…An electron-beam-induced current (EBIC) technique revealed that the minority-carrier diffusion length in single crystalline n-type b-FeSi 2 is approximately 50 lm. 10 In contrast, the minority-carrier diffusion length of b-FeSi 2 films has not been reported. The lower photoresponsivity (and thus shorter minority-carrier diffusion length) in b-FeSi 2 films is probably due to defects at the grain boundaries of b-FeSi 2 epitaxial variants on Si substrates [15][16][17] and high residual carrier (hole) concentrations reaching approximately 10 19 cm À3 at room temperature (RT).…”
Section: Introductionmentioning
confidence: 97%
“…[3][4][5][6][7][8] In particular, a photoresponsivity of over 100 mA/W for 1.31 lm light for n-type b-FeSi 2 single crystals has renewed interest in this material. 9,10 The photoresponsivity obtained for b-FeSi 2 thin films has been increasing each year. [11][12][13][14] However, the highest photoresponsivity obtained so far for b-FeSi 2 thin films (3.3 mA/W at 1.31 lm) 13 is still more than one order of magnitude smaller than that for n-type b-FeSi 2 single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the silicides have good metallic properties there are very few having attractive semiconducting properties. The ␤-phase of iron silicide (␤-FeSi 2 ) is one of the candidates that has the best potential for Si based photovoltaic and optoelectronic applications due to its (i) direct band gap (0.85-0.87 eV) with a wide range of absorption spectrum starting from infrared to visible region [1,2], (ii) higher optical absorption coefficient (>10 5 cm −1 at 1 eV photon energy) compared to that of silicon (of the order of 10 2 cm −1 at 1 eV [2,3]), (iii) long enough hole and electron diffusion length for a specific doping concentration [5,6] and (iv) it can also be grown epitaxially on Si substrate (lattice mismatch only ∼2-5.5%) [6,7]. In addition, it has good physical and chemical stability (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing research on metal silicides during last few years [1][2][3][4][5] for its application in Schottky barriers, ohmic contacts, interface diffusion barriers and photovoltaics. While most of the silicides have good metallic properties there are very few having attractive semiconducting properties.…”
Section: Introductionmentioning
confidence: 99%